Disassembling the Liberal Feminist Legacy of Reproductive Rights in Canada - O'Leary, Maria; Brulé, Elizabeth (Journal of Critical Race Inquiry, 2025)
This article investigates the historical and contemporary exclusions embedded in Canadian reproductive rights discourse through an institutional ethnographic analysis of scholarly literature and state policies on reproduction. We critically engage with the liberal feminist framing of “choice” and “responsible parenthood,” showing how these concepts have historically operated through settler colonial, racial, and cisnormative logics. Drawing on scholarship in Indigenous feminism, Black feminist thought, and trans and queer theory, we trace how reproductive policies in Canada—from eugenics and family planning to abortion access and legal recognition—have systematically marginalized Indigenous, Black, disabled, Two-Spirit, queer and trans people. We argue for a queer, decolonial reproductive justice framework that centers bodily autonomy, community care, and relational accountability beyond liberal legal rights. Informed by institutional ethnography, this article maps how texts, policies, and professional discourses coordinate systemic reproductive oppression while also illuminating activist knowledge and resistance practices that chart a transformative path forward.